Formal Methods for Industrial Critical Systems 15th International Workshop, FMICS 2010, Antwerp, Belgium, September 20-21, 2010. Proceedings - Kowalewski, Stefan; Roveri, Marco; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the proceedings of the 15th International Workshop on Formal Methods for Industrial Critical Systems, FMICS 2010 held in Antwerp, Belgium, in September 2010 - co-located with ASE 2010, the 25th IEEE/ACM International Conference on Automated Software Engineering, The 14 papers presented were carefully reviewed and selected from 33 submissions. The aim of the FMICS workshop series is to provide a forum for researchers who are interested in the development and application of formal methods in industry. It also strives to promote research and development for the improvement of formal methods and tools for industrial applications.
The Metrô Rio ATP Case Study -- Practical Issues with Formal Specifications -- Formal Analysis of BPMN Models Using Event-B -- Developing Mode-Rich Satellite Software by Refinement in Event B -- Automatic Error Correction of Java Programs -- Range Analysis of Microcontroller Code Using Bit-Level Congruences -- An Automated Translator for Model Checking Time Constrained Workflow Systems -- Correctness of Sensor Network Applications by Software Bounded Model Checking -- Model Checking the FlexRay Physical Layer Protocol -- SMT-Based Formal Verification of a TTEthernet Synchronization Function -- Embedded Network Protocols for Mobile Devices -- A Study of Shared-Memory Mutual Exclusion Protocols Using CADP -- A Formal Model of Identity Mixer -- Automatic Structure-Based Code Generation from Coloured Petri Nets: A Proof of Concept.
Keywords: Computer science; Software engineering; Logic design; Computer Science; Software Engineering; Logics and Meanings of Programs; Programming Languages, Compilers, Interpreters; Special Purpose and Application-Based Systems